Transposable element expression in tumors is associated with immune infiltration and increased antigenicity - Yu Kong (Nature Portfolio, 2019)
Treatment with demethylation agents can reactivate transposable elements. Here in glioblastoma, the authors also show that this is accompanied by de novo presentation of TE-derived peptides on MHC class I molecules.